2007
DOI: 10.5194/acp-7-913-2007
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft measurements over Europe of an air pollution plume from Southeast Asia – aerosol and chemical characterization

Abstract: Abstract. An air pollution plume from Southern and Eastern Asia, including regions in India and China, was predicted by the FLEXPART particle dispersion model to arrive in the upper troposphere over Europe on 24-25 March 2006. According to the model, the plume was exported from Southeast Asia six days earlier, transported into the upper troposphere by a warm conveyor belt, and travelled to Europe in a fast zonal flow. This is confirmed by the retrievals of carbon monoxide (CO) from AIRS satellite measurements,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 66 publications
2
56
0
Order By: Relevance
“…Several previous studies have employed AIRS CO to investigate the horizontal extent of combustion products (e.g., Peffers et al, 2009;Zhang et al, 2008;Stohl et al, 2007). AIRS provides ∼70 percent coverage of the Earth's surface on a daily basis (McMillan et al, 2005).…”
Section: Verification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have employed AIRS CO to investigate the horizontal extent of combustion products (e.g., Peffers et al, 2009;Zhang et al, 2008;Stohl et al, 2007). AIRS provides ∼70 percent coverage of the Earth's surface on a daily basis (McMillan et al, 2005).…”
Section: Verification Methodsmentioning
confidence: 99%
“…This inclusion is important since many transport models rely on coarse horizontal scale (e.g., 45-200 km) global meteorological models for their transport parameters (e.g., Stohl et al, 2007;Damoah et al, 2004). Although these models generally have produced satisfactory results, global models do compound interpolation error both spatially and temporally and can produce nonphysical results within transport models (Stohl et al, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances homogeneous nucleation of particles is theoretically possible, and has been observed (e.g., Perry and Hobbs, 1994;Hegg and Baker, 2009;Weigelt et al, 2009). Stohl et al (2007) in particular observed such behavior in SEA air transported to Europe.…”
Section: Convective Pumping and The Summer Monsoonal Anti-cyclonementioning
confidence: 99%
“…Plumes are frequently shown in these papers to reach as far as Taiwan, including the free troposphere receptor site on Lulin Mountain (Wang et al, 2007;Wai et al, 2008;Lin et al, 2009), southern Japan (Tang et al, 2003a,b;Satake et al, 2004) and Hawaii ). Aircraft observations near Europe even identified one exceptionally large IC pollution and smoke event that had traversed 2/3 of the globe (Stohl et al, 2007).…”
Section: Long-range Aerosol Transport In Indo-chinamentioning
confidence: 99%
“…Saharan dust routinely reaches the Amazon, the Caribbean Sea and southeastern U.S. after sweeping over the Atlantic Ocean (Swap et al, 1992;Prospero, 1999;. Asian dust and pollution have long been observed in the western U.S. and beyond (Jaffe et al, 1999;Biscaye et al, 2000;VanCuren and Cahill, 2002;Grousset et al, 2003;Stohl et al, 2007). Microorganisms such as bacteria, fungi, and viruses can be transported along with dust aerosol (Griffin, 2007), raising additional health concern.…”
Section: Aerosol Intercontinental Transport and Its Environmental Impmentioning
confidence: 99%